MELAS: Monitoring treatment with magnetic resonance spectroscopy. (8th October 2018) - Hovsepian, Dominic A.; Galati, Alexandra; Chong, Robert A.; Mazumder, Rajarshi; DeGiorgio, Christopher M.; Mishra, Shri; Yim, Catherine
Abstract: Background: To assess the utility of Magnetic Resonance Spectroscopy (MRS) as a biomarker of response to L‐arginine in mitochondrial encephalomyopathy with lactic acidosis and stroke‐like episodes (MELAS). Aims: To describe a case of MELAS treated with L‐arginine that showed improvement clinically and on serial MRS Methods: MRS was performed on a 1.5‐Tesla scanner to evaluate a MELAS patient before, during, and after intravenous (IV) L‐arginine therapy for the treatment of stroke‐like episodes. L‐arginine was infused at a dose of 500 mg/kg daily for 7 days followed by oral arginine therapy. Results: The patient had clinical improvement after treatment with IV L‐arginine. MRS performed before, during, and after treatment with IV L‐arginine showed significant improvement in brain lactate and increase in the N‐acetylaspartate/Choline (NAA/Cho) ratio compared to pre‐treatment baseline. Conclusion: Serial MRS imaging showed significant improvement in lactate peaks and NAA/Cho ratios that corresponded with clinical improvement after L‐arginine therapy. Given this correlation between radiologic and clinical improvement, MRS may be a useful biomarker assessing response to treatment in MELAS.